God's Babies : Natalism and Bible Interpretation in Modern America - John McKeown
The human population's annual total consumption is not sustainable by one planet. This unprecedented situation calls for a reform of religious cultures that promote a large ideal family size. Many observers assume that Christianity is inevitably part of this problem because it promotes 'family values' and that statistically, in America and elsewhere, Christians have a higher birth rate than non-religious people. This book explores diverse ideas about human reproduction in the church, past and present. It investigates an extreme fringe of U.S. Protestantism, including the Quiverfull movement, that uses Old Testament 'fruitful' verses to support natalist ideas that promote higher fecundity. This book argues that natalism is inappropriate as a Christian application of Scripture, especially since rich populations' total footprints are detrimental to biodiversity and to human welfare.